Making It Big : Why Developing Countries Need More Large Firms - Ciani, Andrea; Hyland, Marie Caitriona; Karalashvili, Nona; Keller, Jennifer L.; Ragoussis, Alexandros; Tran, Trang Thu (Washington, DC: World Bank, 2020)
Economic and social progress requires a diverse ecosystem of firms that play complementary roles. Making It Big: Why Developing Countries Need More Large Firms constitutes one of the most up-to-date assessments of how large firms are created in low- and middle-income countries and their role in development. It argues that large firms advance a range of development objectives in ways that other firms do not: large firms are more likely to innovate, export, and offer training and are more likely to adopt international standards of quality, among other contributions. Their particularities are closely associated with productivity advantages and translate into improved outcomes not only for their owners but also for their workers and for smaller enterprises in their value chains. The challenge for economic development, however, is that production does not reach economic scale in low- and middle-income countries. Why are large firms scarcer in developing countries? Drawing on a rare set of data from public and private sources, as well as proprietary data from the International Finance Corporation and case studies, this book shows that large firms are often born large—or with the attributes of largeness. In other words, what is distinct about them is often in place from day one of their operations. To fill the “missing top” of the firm-size distribution with additional large firms, governments should support the creation of such firms by opening markets to greater competition. In low-income countries, this objective can be achieved through simple policy reorientation, such as breaking oligopolies, removing unnecessary restrictions to international trade and investment, and establishing strong rules to prevent the abuse of market power. Governments should also strive to ensure that private actors have the skills, technology, intelligence, infrastructure, and finance they need to create large ventures. Additionally, they should actively work to spread the benefits from production at scale across the largest possible number of market participants. This book seeks to bring frontier thinking and evidence on the role and origins of large firms to a wide range of readers, including academics, development practitioners and policy makers.